Soil depth and precipitation moderate soil textural effects on seedling survival of a foundation shrub species. Issue 6 (2nd May 2022) - Veblen, Kari E.; Nehring, Kyle C.; Duniway, Michael C.; Knight, Anna; Monaco, Thomas A.; Schupp, Eugene W.; Boettinger, Janis L.; Villalba, Juan J.; Fick, Stephen; Brungard, Colby; Thacker, Eric
Abstract : In drylands, there is a need for controlled experiments over multiple planting years to examine how woody seedlings respond to soil texture and the potentially interactive effects of soil depth and precipitation. Understanding how multiple environmental factors interactively influence plant establishment is critical to restoration ecology and in this case to broadscale restoration efforts in western U.S. drylands dominated by big sagebrush ( Artemisia tridentata ). We planted sagebrush seedlings across a range of soil textures and depths in the southern portion of the species' range, on the Colorado Plateau, USA. We evaluated survival of repeated plantings of caged and uncaged seedlings over 2 years across 20 plots in wet versus average precipitation years at one site, and examined broader patterns of sagebrush seedling survival during an average precipitation year in 56 plots across four sites. First‐year survival was >9× higher under wet than average precipitation. Under favorable (wet) conditions, early sagebrush seedling survival was highest on coarser soils, especially those that also had a shallower restrictive layer (e.g. 50–100 cm). Under average precipitation, soil texture and depth effects on survival of newly planted seedlings were much weaker, but older (>1 year) seedlings benefitted from growing on coarser‐textured soils. It may be possible to increase survival by sheltering seedlings with small mesh cages, which likely improve moisture availability. Our results provide new insights into environmental factors that limit woody seedling survival in drylands and illustrate that planting in wet years and incorporating detailed soil setting information could increase survival of sagebrush seedlings in restoration projects.